Slametan Event On New Year's Eve New In Strengthening Solidarity Boyolali Village Community - Linda Khofifah (International Journal of Sociology of Religion, 2023)
New Year, become great night  often used by some  teenager For do matter negative things like drunk , do matter deviate and stuff others can raises chaos and chaos. Then what, activities positive done at night year new. Slametan be one activities carried out by some public Java as expression of gratitude nor safety to god, In order strengthen connection between fellow citizens  boyolali in the village Boyolali, held a Gathering event Slametan at night day on date final before enter year new. Research methods This use study qualitative related to Max Weber's Theory action social. Based on results research , as for values solidarity embodied and benefits  from gatherings  Slametan ie First Strengthen familiarity, Second Strengthen Solidarity between fellow, Third increase the religiosity of Boyolali residents, Fourth, Stretch Conflict Fourth Increase harmony among residents of Boyolali Village, Central Java.